Letter: is pneumococcal vaccination safe during the COVID‐19 pandemic? Authors' reply. Issue 5 (14th August 2020) - Al‐Ani, Aysha H.; Johnson, Doug; Christensen, Britt
Abstract : LINKED CONTENT This article is linked to Al‐Ani et al and Deniz et al papers. To view these articles, visit https://doi.org/10.1111/apt.15779 and https://doi.org/10.1111/apt.15903